A novel strong ground motion duration to reduce computation time of structural time history analysis. Issue 164 (January 2023) - He, Yiting; Li, Shuang; Wei, Yuliang; Xie, Lili
Abstract: As a widely used dynamic computation method for seismic response analysis of structures, time history analysis (THA) can be a time-consuming procedure in some situations. In order to reduce the calculation time, this study proposed a novel strong ground motion duration which can truncate the head and tail weak signals of records before THA. The initial point of proposed duration refers to the concept of bracketed duration, while the termination point is determined by the maximum displacement responses of equivalent single-degree-of-freedom (SDOF) systems of the structure. The relationship between the fundamental period and period-lengthening level of structure is counted from previous research and fitted with a formula which is used to compute the period range of equivalent SDOF systems. After comparing the structural responses and time-saved percentage of truncated records by proposed duration with those by other definition of durations, results prove that the proposed duration has significant time-saving procedure and reliable computation results on THA. Highlights: A novel strong ground motion duration is proposed to save computation time. The duration is used to truncate ground motion records before dynamic analysis. Relation of structural fundamental period and period elongation ratio is studied. Truncated records by the duration keep structural responses almost unchanged. The duration is the best on balancing efficiency and accuracy compared with others.